2021
DOI: 10.1186/s13643-021-01604-w
|View full text |Cite
|
Sign up to set email alerts
|

Mapping evidence of depression in HIV-seropositive MSM in sub-Saharan Africa: a scoping review protocol

Abstract: Background Depression is one of the most prevalent mental disorders among an estimated 25.6 million people living with HIV (PLHIV) in sub-Saharan Africa (SSA). The depression rate is higher in HIV-seropositive men who have sex with men (MSM) regardless of their sexual orientation, identity or romantic attraction. This is due to various types of stigma including HIV-related stigma, social stigma, self-stigma and mental health stigma. Opportunistic infections, unemployment, poverty and food insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…All authors will also regularly engage in re exive meetings to discuss and minimise biases, resolve disagreements, and reach consensus. Quantitative data from studies will be analyzed using numerical counts and tables 36 . Findings will then be used to summarise current literature on H-MSM, identify research gaps and future directions, and re ect on the feasibility of a systematic review or future primary studies.…”
Section: Charting the Datamentioning
confidence: 99%
“…All authors will also regularly engage in re exive meetings to discuss and minimise biases, resolve disagreements, and reach consensus. Quantitative data from studies will be analyzed using numerical counts and tables 36 . Findings will then be used to summarise current literature on H-MSM, identify research gaps and future directions, and re ect on the feasibility of a systematic review or future primary studies.…”
Section: Charting the Datamentioning
confidence: 99%
“…Prolonged psychological distress increases the risk of other adverse health outcomes, such as coronary heart disease (Cohen et al, 2007). Although numerous studies have found MSM to have higher depression rates than their heterosexual counterparts (Ulanja et al, 2019;Mulqueeny et al, 2021), lim-ited research about the experiences of MSM refugees and asylum seekers with depression is available. Nevertheless, consistent with other emerging research, our study indicates the need to understand further specific mental health disparities among MSM refugees and asylum seekers in Kenya.…”
Section: Asylum and Refugee Application Processmentioning
confidence: 99%
“…Littlewood, Chance-Larsen and McLean (2010) suggest that "inadequate attention to key design features including sample size, allocation and level of blinding" may increase inaccurate conclusions (23). Therefore, the quality of collected literature will be appraised through ratings from high average (100%) to above average (75%), average (50%) and lowquality (25%) research evidence (24).…”
Section: Qualitymentioning
confidence: 99%